Pengaruh Knowledge sharing, Motivasi Kerja, dan Etos Kerja Terhadap Kinerja Pegawai Dinas Perhubunggan Kota Semarang - Wakhidatun Nafaah; Qristin Violinda; Rauly Sijabat (Jurnal Ilmiah Manajemen, Bisnis dan Kewirausahaan, 2026)
The performance of Semarang City Transportation Agency employees not only affects the smooth operation of the transportation sector but also directly affects the quality of public services received by the community. The purpose of this study is to analyze the influence of knowledge sharing, work motivation and work ethic on the performance of Semarang City Transportation Agency employees. The method used by the researcher is a quantitative research method. The data collection technique is through a questionnaire. The data analysis techniques used are the classical assumption test, the f test and the hypothesis test. The results of this study can be concluded that knowledge sharing, work motivation and work ethic have a positive and significant effect on employee performance with a significance value of 0.000 and this value is smaller than 0.05.